Can we Monitor a Patient with Inflammatory Bowel Disease and Adapt Treatment without Endoscopy? - Panes, Julian; Ricart, Elena (Current Drug Targets, 2018)
Background: While predictors of disease course in inflammatory bowel diseases (IBD) are not accurate, we adapt therapies reactively, after objective demonstration of the presence of active disease, complications, or an inadequate response to a therapeutic intervention. In this context, adequate monitoring is essential to make timely management decisions. Objective: To review the role of clinical assessment, biomarkers, radiology and endoscopy in monitoring patients with IBD. Results: Assessment of clinical symptoms is the cornerstone of monitoring in IBD; in ulcerative colitis (UC) there is acceptable correspondence between mucosal lesions and presence of symptoms, but in Crohn's disease (CD) there is a considerable disconnection between these two, and monitoring requires complementary tests. Blood and stool markers such as C-reactive protein and fecal calprotectin are increasingly used. However, the operating properties of these biomarkers are different according to disease type (UC vs. CD), age (pediatric or adult), and disease location (small bowel vs. colonic disease). Cross-sectional imaging has a similar accuracy to endoscopy to detect inflammation in CD, and a higher accuracy to detect stenosing and penetrating complications. It has also been shown that magnetic resonance imaging is accurate for measuring response to therapeutic interventions. Conclusion: Cross-sectional imaging is one of the preferred monitoring options in patients with CD. Endoscopy continues to be the preferred examination for assessing UC, and should still be considered in patients with CD who have symptoms or altered biomarkers and cross-sectional imaging is negative.
Keywords: ultrasonography